2006
DOI: 10.5210/fm.v11i8.1386
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards shareable metadata

Abstract: A focus of digital libraries, particularly since the advent of the Open Archives Initiative Protocol for Metadata Harvesting, is aggregating from multiple collections metadata describing digital content. However, the quality and interoperability of the metadata often prevents such aggregations from offering much more than very simple search and discovery services. Shareable metadata is metadata which can be understood and used outside of its local environment by aggregators to provide more advanced services. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 5 publications
1
26
0
1
Order By: Relevance
“…In addition, these additional fields used provided descriptive information about the resources that was more specific and nuanced than could be achieved using standard Dublin Core elements. However, consistent with findings from Jackson et al (2008) and Shreeves et al (2006), we found that the frequent use of unique fields that make native metadata rich in context can impede interoperability if the field names are too unique and specific. This is because the contextual information associated with fields in the local environment, including more fulsome labeling, will be lost when the metadata is harvested by aggregators in Dublin Core format.…”
Section: Conclusion and Recommendationssupporting
confidence: 79%
See 4 more Smart Citations
“…In addition, these additional fields used provided descriptive information about the resources that was more specific and nuanced than could be achieved using standard Dublin Core elements. However, consistent with findings from Jackson et al (2008) and Shreeves et al (2006), we found that the frequent use of unique fields that make native metadata rich in context can impede interoperability if the field names are too unique and specific. This is because the contextual information associated with fields in the local environment, including more fulsome labeling, will be lost when the metadata is harvested by aggregators in Dublin Core format.…”
Section: Conclusion and Recommendationssupporting
confidence: 79%
“…For this reason, although the mapping seemed right in a broad sense, such as <country> to <spatial> and <local call number> to <identifier>, information displayed in the aggregators' environments can seem confusing and ambiguous to users. Unless values in the more specific locally defined field are carefully crafted, mapping for a granular local field to a more generalized Dublin Core element cannot convey the same precise, unambiguous meaning as it does in locally customized applications (Shreeves et al, 2006). We recommend that fields useful only in the local context (e.g., local call number) are not exported to service providers.…”
Section: Specificity and Granularitymentioning
confidence: 99%
See 3 more Smart Citations